Dissatisfied Creators: Generating Creative Ideas Amid Negative Emotion in Health Care. Issue 2 (May 2020) - Lee, Yuna S. H.; Nembhard, Ingrid M.; Cleary, Paul D.
Improving performance often requires creative ideas in extreme work settings like health care. Frontline workers are promising sources of creative ideas. The authors assert that their job dissatisfaction is positively associated with creativity in health care settings because negative emotion spurs creativity when tied to engaging work and that characteristics such as shorter tenure, greater role centrality, and high boundary spanning can strengthen this relationship. The authors find supporting evidence in data on ideas generated over 18 months by health professionals in 12 clinics. Results suggest that health care organizations should not overlook dissatisfied workers as valuable sources of creative improvement ideas.